The Law of One Price Over 700 Years - Rogoff, Kenneth (IMF Working Papers; Working Paper, 2001)
This paper examines annual commodity price data from England and Holland over a span of seven centuries. Our data incorporates transaction prices on seven commodities: barley, butter, cheese, oats, peas, silver, and wheat, as well as pound/shilling nominal exchange rates going back, in some cases, to 1273. We find that the magnitude, volatility, and persistence of deviations from the law of one price have not declined by as much as one might expect. We find this despite lower transport costs, reduced trade protection, and fewer wars and plagues in the modern era. Our analysis is consistent with growing evidence that goods-market arbitrage remains highly imperfect, even today.